1980
DOI: 10.1021/bi00542a001
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical proton gradient in inverted membrane vesicles from Escherichia coli

Abstract: Inverted membrane vesicles prepared from Escherichia coli ML 308-225 generate a transmembrane electrochemical proton gradient (delta mu H+; interior positive and acid) during oxidation of D-lactate, succinate, reduced phenazine methosulfate, or NADH or hydrolysis of ATP. Using the distribution of the lipophilic anion thiocyanate to measure the membrane potential (delta psi) and the permeant weak base methylamine to measure the pH gradient (delta pH), maximal values for delta psi H+ of approximately +160 mV are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
110
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 55 publications
7
110
0
Order By: Relevance
“…15 Second, the respiratory control ratio (RCR) is the ratio of the coupled and uncoupled rates of catalysis: Δ p opposes catalysis, so when an “uncoupler” is used to dissipate Δ p , the rate increases. The RCR value for NADH oxidation by Q 10 PLs (1.1, 4 H + translocated per NADH) is low compared to values reported for submitochondrial particles (3.0–5.5,11, 12, 16 10 H + per NADH for complexes I, III, and IV) and complex I containing PLs measured using DQ (2.2–4.5,17, 18 4 H + per NADH) However, lower values are typical for succinate oxidation by SMPs (1.6–3.2,11, 12, 16 6 H + per succinate from complexes II, III and IV), and the highest value from inverted Escherichia coli vesicles that are known to sustain Δ p ≈160 mV19 is 1.720 (6 H + per NADH, from complex I and an ubiquinol oxidase). Higher RCR values are usually taken to indicate “better coupled” vesicles, but the values are also affected by the enzyme activity and configuration.…”
mentioning
confidence: 98%
“…15 Second, the respiratory control ratio (RCR) is the ratio of the coupled and uncoupled rates of catalysis: Δ p opposes catalysis, so when an “uncoupler” is used to dissipate Δ p , the rate increases. The RCR value for NADH oxidation by Q 10 PLs (1.1, 4 H + translocated per NADH) is low compared to values reported for submitochondrial particles (3.0–5.5,11, 12, 16 10 H + per NADH for complexes I, III, and IV) and complex I containing PLs measured using DQ (2.2–4.5,17, 18 4 H + per NADH) However, lower values are typical for succinate oxidation by SMPs (1.6–3.2,11, 12, 16 6 H + per succinate from complexes II, III and IV), and the highest value from inverted Escherichia coli vesicles that are known to sustain Δ p ≈160 mV19 is 1.720 (6 H + per NADH, from complex I and an ubiquinol oxidase). Higher RCR values are usually taken to indicate “better coupled” vesicles, but the values are also affected by the enzyme activity and configuration.…”
mentioning
confidence: 98%
“…This transport was inhibited by the addition of EIPA, an inhibitor of Na ϩ /H ϩ antiporters (21). However, data obtained with E. coli wild-type cells and membrane vesicles indicated the presence of an NADH-induced proton gradient (10,22,23). In addition, FT-IR spectroscopy has shown that the redox reaction of the E. coli complex I is associated with the protonation of tyrosines and acidic amino acids (24,25).…”
mentioning
confidence: 99%
“…E. coli UTL2mdfA::kan cells overexpressing MdfA were grown and treated as described (15). Inverted membrane vesicles were prepared from these cells as described (18). Cells were washed once in 50 mM potassium phosphate, pH 7.5͞5 mM MgSO 4 .…”
mentioning
confidence: 99%